Pengembangan Bahan Ajar Digital Berbasis Kearifan Lokal Tari Lenggang Cisadane untuk Meningkatkan Kemampuan Membaca Pemahaman dan Karakter Saling Menghargai di Sekolah Dasar - Yuliyanti Yuliyanti; Yuyu Yuhana; Ratna Sari Dewi (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The objective of this result is To ascertain the academic achievements of students subsequent to the implementation of digital instructional materials derived from the traditional Lenggang Cisdanee dance to enhance reading comprehension and foster respect for the textual content (explanation) at the elementary level, specifically in the fifth grade. The type of research employed is development research (R&D). The research and development method, or Research and Development, is a research method used to produce specific products and to test their effectiveness and the effectiveness of the development process. The results of calculations using N-Gain fall within the effective category, indicating that students exhibit an increase in learning outcomes. This is evidenced by the lower pre-test value in comparison to the post-test value following the utilisation of digital teaching materials based on the local wisdom of the Lenggang Cisadane dance. The response of students to digital teaching materials based on the local wisdom of the Lenggang Cisadane dance is highly positive. Students' learning outcomes have demonstrably improved following the use of digital teaching materials based on the local wisdom of the Lenggang Cisadane dance.